UPLC–ESI–QTOF–MS profiling, antioxidant, antidiabetic, antibacterial, anti-inflammatory, antiproliferative activities and in silico molecular docking analysis of Barleria strigosa - Ming Lei; Lei Wang; Oladipupo Odunayo Olatunde; Sudarshan Singh; Chitchamai Ovatlarnporn; Abdul Basit; Opeyemi Joshua Olatunji (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background This study investigated the in vitro antidiabetic, antioxidant, antibacterial, anti-inflammatory and antiproliferative effects of B. strigosa hydrophilic (BSTR) and lipophilic (LSB) leaves extracts. The phytochemical profile was also performed using UHPLC–ESI–QTOF–MS. Results The results indicated that BSTR and LSB showed excellent antioxidant properties in the DPPH scavenging, ABTS scavenging, FRAP and MCA assays. The extracts also demonstrated α-glucosidase (81.56–157.56 µg/mL) and α-amylase (204.44 µg/mL) inhibitory activities. In addition, the extracts showed significant cytotoxic and antiproliferative effects against oral squamous carcinoma (CLS-354/WT) cancer cells. Furthermore, the extracts showed excellent antibacterial activity against Listeria monocytogenes, Vibrio parahaemolyticus, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. Both extracts exhibited a significant reduction in nitric oxide secretion against activated macrophage cells. The UHPLC–MS analysis revealed that B. strigosa is rich in terpenoids, iridoid glycosides, flavonoids, and phenolic compounds. The plethora of these compounds may be responsible for the observed activities. In addition, the bioactive compounds identified by UHPLC–ESI–QTOF–MS were analyzed using silico molecular docking studies to determine the binding affinity with α-amylase and α-glucosidase. Conclusions These results suggest that B. strigosa is an excellent pharmacological active plant and it provides the basis for further studies on the exploration of its potentials in oxidative stress induced disorders. Graphical Abstract